The digital simulation and fuzzy evaluation to reduce the likelihood of unsafe behavior in nuclear decommissioning. (September 2018) - Li, Meng-kun; Liu, Yong-kuo; Peng, Min-jun; Xie, Chun-li; Yang, Li-qun
Highlights: A method for evaluating safety of behavior of virtual human a trainee controlled in digital simulation was proposed. A safety evaluation and simulation software was developed. A primary virtual training method to reduce chance of unsafe behavior was proposed. Abstract: Workers' behavior during the dynamic process of nuclear decommissioning is a complex phenomenon. In a nuclear environment, some workers may spontaneously and inadvertently engage in unsafe behavior which has high risks of serious injury and accident. In this paper, we determined and classified some of the unsafe behavior of workers in the nuclear decommissioning process. The evaluation factor system and the AHP model were established. The safety of behavior of virtual human, a trainee controlled in digital simulation, was quantified by fuzzy evaluation method. A primary virtual training method to reduce the chance of unsafe behavior was proposed and a safety training simulation software was developed. The feasibility of the proposed methods was tested through a hypothetical case.